PENERAPAN MOTION TWEEN UNTUK ANIMASI DUA DIMENSI RUTE PERJALANAN BUS TRANS JOGJA - Nugrahenny, Dwi; Honggowibowo, Anton Setiawan; Mukti, Mega Lesya (Institut Teknologi Dirgantara Adisutjipto, 2013)
TransportationÂ isÂ oneÂ ofÂ theÂ importantÂ aspectsÂ inÂ aÂ region,Â whereÂ public transportationÂ takeÂ effectÂ onÂ theÂ mobilityÂ ofÂ theÂ people.Â ToÂ achieveÂ aÂ good transportation can be create, so that the infrastructure and other supporting factors areÂ needed. Yogyakarta municipalityÂ areaÂ hasÂ a lotÂ ofÂ public transportasion,Â oneÂ of themÂ isÂ â€œTransÂ Jogjaâ€Â bus,Â whereÂ eachÂ busÂ lineÂ hasÂ itsÂ routeÂ toÂ reachÂ any destination.Â ItÂ isÂ neededÂ aÂ supportingÂ mediaÂ thatÂ canÂ provideÂ informationÂ aboutÂ the route for each bus line so that people can be easily deciding which bus line that can use to reach their destination. Those information presented in the form of animation withÂ anÂ interestingÂ andÂ informativeÂ media.Â TheÂ useÂ ofÂ animationÂ asÂ anÂ information mediaÂ thatÂ shownÂ asÂ aÂ routeÂ trip,Â busÂ lineÂ includingÂ busÂ stopÂ andÂ departing passangersÂ placeÂ assessedÂ canÂ beÂ useÂ asÂ oneÂ ofÂ theÂ otherÂ optionÂ forÂ obtaining information except from a conventional map.